Pengaruh Perbandingan Pelarut Etanol-Air Terhadap Kadar Senyawa Fenolat Total dan Daya Antioksidan dari Ekstrak Daun Sirsak (Annona muricata L.) - Rivai, Harrizul; S, Ernita Widiya; Rusdi, Rusdi (Jurnal Sains dan Teknologi Farmasi, 2013)
A Study has been conducted to determine the influence of ethanol-water ratio on the concentration of total phenolic compounds and antioxidant activities of extract of soursop leaves. Ethanol-water ratio used were ethanol 96%, ethanol-water 2:1 and ethanol-water 1:1. Concentration of phenolic compounds were determined by Folin-Ciocalteau method and antioxidant activities were detemined by diphenylpicrylhydrazyl method. Results showed that the ratio of ethanol-water had a significant influence on the total content of phenolic compounds (p < 0.05). Highest content of total phenolic compound was obtained by using ethanol-water 1:1, whereas the highest antioxidant activity was obtained by using ethanol 96%.